Synthesis of 3-substituted isoxazolidin-4-ols using hydroboration–oxidation reactions of 4,5-unsubstituted 2,3-dihydroisoxazoles - Dikošová, Lívia; Laceková, Júlia; Záborský, Ondrej; Fischer, Róbert (Beilstein Journal of Organic Chemistry, 2020)
Isoxazolidines represent a very important class of N/O-containing heterocycles used as the key intermediates in the synthesis of more complex cyclic and acyclic compounds, including various biologically active molecules. Here, we present a fast and highly stereoselective approach towards both C-3/4-cis and C-3/4-trans isomers of 3-substituted isoxazolidin-4-ols. The strategy relies on a highly regio- and trans-stereoselective hydroboration–oxidation reaction of the 4,5-unsubstituted 2,3-dihydroisoxazoles with basic hydrogen peroxide. The consecutive oxidation/reduction route, sequentially employing Dess–Martin periodinane and ʟ-selectride, is used for the inversion of the C-3/4-trans relative configuration of the isoxazolidine ring. The significance of the method lies in its variability and applicability to a concise synthesis of various 4-hydroxyisoxazolidines, starting from the readily available C-alkyl/aryl-nitrones. The resemblance to 3-hydroxypyrrolidines certainly makes the 4-hydroxyisoxazolidines important and valuable structural fragments in drug discovery.
Keywords: 2,3-dihydroisoxazoles; diastereoselectivity; heterocycles; hydroboration–oxidation; isoxazolidin-4-ols